Effectiveness of giving warm ginger in reducing the frequency of nausea and vomiting in first trimester pregnant women - Ida Royani; Indri Afiska; Febie Irsandy Syahruddin; Fadli Ananda; Irna Diyana Kartika K (Jurnal EduHealth, 2024)
Nausea and vomiting (emesis) are typical joint symptoms in pregnancy. Nausea usually occurs in the morning but can also occur at any time of the night. Nausea and vomiting occur in 60-80% of primigravida and 40-60% of multigravida. Emesis gravidarum can interfere with daily activities and can even be dangerous for the mother and fetus. One of the complications of nausea and vomiting during pregnancy that is very dangerous for pregnant women and can have an impact on maternal and fetal death is excessive nausea and vomiting that continues to become hyperemesis gravidarum. Nausea and vomiting during pregnancy are felt by 50%-90% of pregnant women. Nausea and vomiting generally only occur in the first trimester of pregnancy, but 20% of women experience these symptoms throughout pregnancy that can interfere with daily activities. Quasy experiment with Pretest Posttest One Group design with 13 respondents. The work subjects of this study have a junior high school education level, all pregnant women are multigravida, and the majority are IRT. It was also found that the mean age of the research subjects was 26.0 ± 5.29 years and had a gestational age of 9.69 ± 2.28 months. The results showed that before the intervention, the average frequency of nausea and vomiting was 8 ± 2.34 times, while after the intervention, the average frequency was 5.0 ± 1.87 times. In addition, there was a decrease in the frequency of nausea and vomiting after the intervention by 3.0 ± 1.77 times. In this study involving 13 respondents, it was shown that the administration of 200 mL of ginger drink with a frequency of twice a day for one day was effective in reducing the intensity of nausea and vomiting in first-trimester pregnant women